PENGARUH MODEL PEMBELAJARAN EXPERIENTIAL LEARNING DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VIII SMP SWASTA SANTO PETRUS MEDAN TAHUN PEMBELAJARAN 2024/2025: Penelitian Kuantitatif - Siagian, Krisna Yosef Alosius; Asnita Hasibuan; Candra Ronitua Gultom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the experiential learning model on the writing skills of observation report texts among eighth-grade students at SMP Swasta Santo Petrus Medan in the 2024/2025 academic year. This research used a quantitative approach with an experimental method and a pretest-posttest control group design. The sample consisted of 65 students, with class VIII-3 as the experimental group and class VIII-4 as the control group. The instruments used included writing tests (pretest and posttest) and student response questionnaires regarding the learning model. The results indicated a significant improvement in students' writing skills who were taught using the experiential learning model compared to those taught with conventional methods. Furthermore, the questionnaire results showed that students responded positively to the experiential learning model, as it was perceived to enhance understanding, creativity, and active engagement in the learning process. Thus, the experiential learning model proved to be effective in improving students' skills in writing observation report texts.